Non-pharmacologic treatment of arterial hypertension - Sosa-Rosado, José Manuel (2010)
Modifications in life style must be recommended to hypertensive patients, with strategies limiting salt and alcohol consumption, performing aerobic exercises, consumption of fruits, vegetables and low fat milk products in order to obtain a suitable weight. In the present article we essay on adjustment of these dietetic recommendations in our country.